An integrative and dynamic approach for monographing species-rich plant groups – Building the global synthesis of the angiosperm order Caryophyllales - Borsch, Thomas (2015)
One of the major goals of systematics is to provide a synthesis of knowledge on the diversity of a group of organisms, such as flowering plants. Biodiversity conservation and management call for rapid and accurate global assessments at the species level. At the same time the rapid development of evolutionary biology with a spectrum of approaches to test species relationships and species limits, has revolutionised and is still revolutionizing the science of plant systematics including taxonomy. We explore the relevant scientific and technological developments with the aim to suggest a conceptual framework for an integrated monographic synthesis which can reach global coverage. Our exemplar group are the Caryophyllales, which are a lineage of worldwide distribution, comprising approx. 5% of flowering plant species diversity. The current situation of classification is marked by a transition from pre-phylogenetic treatments to taxonomic treatments increasingly evaluated in an evolutionary context. Structured data (both molecular and morphological), linked to well-documented specimens will be important as fundamental entities of information that can be subjected to evolutionary analysis. As a result, taxon concepts are established as hypotheses which then can be used as basis for a classification system in a second step. Global syntheses need to provide information and use a classification system that reflects the current state of knowledge. In order to accommodate the constantly improved understanding of the organisms, eventually also resulting in the change of taxon concepts, the treatments need to be dynamic. The workflow for a global monographic synthesis as outlined here is supported by currently available biodiversity informatics tools such as the EDIT Platform for Cybertaxonomy. The availability of electronic sources (names, protologues, type images, literature) greatly facilitates the access to information, but as our case shows, considerable efforts for data curation and research are still needed. The implementation of a global monographic synthesis such as the Caryophyllales requires the involvement of the global scientific community.